(untitled) (Eurasian Medical Research Periodical, 2022)
Climatic conditions and soil characteristics in different regions of the country and pathogenic in the treatment of cylindrosporiosis, flour-dew, chlorosis, leaf wrinkles (curly), fungal diseases caused by bacterial, viral, fungal and fungal infections, despite the high level of immunity to various infectious and non-infectious diseases under the influence of pathogenic microorganisms due to environmental factors depending on the type of application, drugs can be used to grow nutritious leaves for the healthy development of mulberry sprouts, seedlings, adult trees and intensively nutritious mulberry trees